A Worldwide Survey on Peyronie's Disease Surgical Practice Patterns Among Surgeons. Issue 4 (14th March 2018) - Chung, Eric; Wang, Run; Ralph, David; Levine, Laurence; Brock, Gerald
Abstract: Background: Despite published guidelines on Peyronie's disease (PD), there are limited data on actual surgical practice among surgeons. Aim: To evaluate the surgical practice patterns in PD among surgeons from different continents and members of various sexual medicine societies. Methods: An anonymous survey on various pre-, intra-, and postoperative aspects of PD surgical care was distributed in printed format during International Society of Sexual Medicine meetings and as an online survey to International Society of Sexual Medicine members. Outcomes: 390 surgeons responded to the survey, with great variations in pre-, intra-, and postoperative strategies in PD surgical care. Results: Most surgeons performed fewer than 10 penile plications and 10 graft surgeries per year. Modified Nesbit plication was the preferred option by most surgeons. Surgeons who received fellowship training were more likely to perform autologous than allograft surgery (odds ratio = 1.79, 95% CI = 1.13–2.82, P = .01). The use of penile color duplex ultrasound was inconsistently performed, with higher-volume surgeons (ie, >20 cases operated a year) more likely to use this diagnostic modality (odds ratio = 70.18, 95% CI = 20.99–234.6, P < .001). Most surgeons agreed that surgical intervention should be performed only after a 6-month history of stable penile curvature, although higher-volume surgeons were more inclined to perform surgery sooner ( P = .08). Clinical Implications: Although it is unknown whether variations in PD surgery significantly affect clinical outcome and patient satisfaction rate, this worldwide survey study has the potential to assist in the formation of a new practice guideline and serve as the basis for future prospective multinational studies. Strength and Limitations: This is one of the largest surveys on PD practice and, to our knowledge, the only survey conducted across various sexual medicine societies, with the inclusion of many high-volume and experienced PD surgeons. This also is the 1st study to comprehensively evaluate many key aspects in surgical practice patterns for PD. However, the categorization on the questionnaire used in this survey was not designed to allow for direct comparison given the possibility of some surgeons with dual society memberships, reporting biases, large CIs in outcomes, different patient demographics, and cultural acceptance. Conclusion: There is great variation in surgical practice patterns in PD management, including key differences among surgeons across different continents and sexual medicine societies.